Long and short-term effects of the financial crisis on labour productivity, capital and output - Oulton, Nicholas; Sebastiá-Barriel, María (London, 2013)
"The behaviour of labour productivity in the United Kingdom since the onset of the recession in early 2008 constitutes a puzzle. Over four years after the recession began labour productivity is still below its previous peak level. This paper considers the hypothesis that economic capacity can be permanently damaged by financial crises. A model which allows a financial crisis to have both a short-run effect on the growth rate of labour productivity and a long-run effect on its level is estimated on a panel of 61 countries over 1955-2010. The main finding is that a banking crisis as defined by Reinhart and Rogoff on average reduces the short-run growth rate of labour productivity by between 0.6% and 0.7% per year and the long-run level by between 0.84% and 1.1% (depending on the method of estimation), for each year that the crisis lasts. A banking crisis also reduces the long-run level of capital per worker by an average of about 1%. The effect on GDP per capita is about double the effect on GDP per worker since there is a long-run, negative effect on the employment ratio."